Poorly Differentiated Clusters Predict Colon Cancer Recurrence: An In-Depth Comparative Analysis of Invasive-Front Prognostic Markers. (June 2018) - Konishi, Tsuyoshi; Shimada, Yoshifumi; Lee, Lik Hang; Cavalcanti, Marcela S.; Hsu, Meier; Smith, Jesse Joshua; Nash, Garrett M.; Temple, Larissa K.; Guillem, José G.; Paty, Philip B.; Garcia-Aguilar, Julio; Vakiani, Efsevia; et al.
Abstract : This study aimed to compare common histologic markers at the invasive front of colon adenocarcinoma in terms of prognostic accuracy and interobserver agreement. Consecutive patients who underwent curative resection for stages I to III colon adenocarcinoma at a single institution in 2007 to 2014 were identified. Poorly differentiated clusters (PDCs), tumor budding, perineural invasion, desmoplastic reaction, and Crohn-like lymphoid reaction at the invasive front, as well as the World Health Organization (WHO) grade of the entire tumor, were analyzed. Prognostic accuracies for recurrence-free survival (RFS) were compared, and interobserver agreement among 3 pathologists was assessed. The study cohort consisted of 851 patients. Although all the histologic markers except WHO grade were significantly associated with RFS (PDCs, tumor budding, perineural invasion, and desmoplastic reaction: P <0.001; Crohn-like lymphoid reaction: P =0.021), PDCs (grade 1 [G1]: n=581; G2: n=145; G3: n=125) showed the largest separation of 3-year RFS in the full cohort (G1: 94.1%; G3: 63.7%; hazard ratio [HR], 6.39; 95% confidence interval [CI], 4.11-9.95; P <0.001), stage II patients (G1: 94.0%; G3: 67.3%; HR, 4.15; 95% CI, 1.96-8.82; P <0.001), and stage III patients (G1: 89.0%; G3: 59.4%; HR, 4.50; 95% CI, 2.41-8.41; P <0.001). PDCs had the highest prognostic accuracy for RFS with the concordance probability estimate of 0.642, whereas WHO grade had the lowest. Interobserver agreement was the highest for PDCs, with a weighted kappa of 0.824. The risk of recurrence over time peaked earlier for worse PDCs grade. Our findings indicate that PDCs are the best invasive-front histologic marker in terms of prognostic accuracy and interobserver agreement. PDCs may replace WHO grade as a prognostic indicator. Abstract : Supplemental Digital Content is available in the text.